Novel simultaneous assessment of contact force and local impedance for radiofrequency catheter ablation guidance. (24th May 2021) - Alken, FA; Scherschel, K; Masjedi, M; Grebe, O; Meyer, C
Abstract: Funding Acknowledgements: Type of funding sources: None. Background:  Contact force (CF) and local impedance (LI) have been separately established for radiofrequency (RF) catheter ablation guidance, enabling estimation of mechanical catheter stability and underlying electrical tissue substrate properties, respectively. However, simultaneous investigation for evaluation of combined electromechanical coupling during RF energy delivery has not been conducted in-human.  Purpose:  Evaluation of the relationship of CF to LI during catheter-based RF atrial fibrillation / tachycardia ablation.  Methods:  In this explorative study, patients presenting with recurrent atrial fibrillation and/or atrial tachycardia for ablation after previous index AF ablation were enrolled. A novel open-irrigated single-tip ablation catheter capable of continuously assessing CF and LI was used after initial high-density mapping. Baseline LI, CF and local bipolar voltage were assessed for each ablation site, with subsequent analysis of mean CF and the force-time integral (FTI) during ablation as well as the maximum LI drop (ΔLI), reflecting acute lesion formation during RF delivery. Results:  In 11 patients [n = 5 female, mean age 66 ± 11 years, median previous procedures n = 2 (interquartile range 1-2)], overall 364 RF energy deliveries were analysed after exclusion of lesions indicating catheter instability or lesions with a RF-duration <10 s. Acute procedural success was reached in all patients, with no periprocedural complications observed.  CF showed a weak correlation to baseline LI during linear regression analysis (r = 0.29, p < 0.001). Baseline LI as well as ΔLI were higher in regions of high (>0.5 mV) vs intermediate (0.1–0.5 mV) or low (<0.1 mV) voltage (baseline LI: p < 0.001, ΔLI: p = 0.04). The ΔLI was more strongly related to baseline LI (r = 0.38, p < 0.001) compared to mean CF / FTI during ablation (r = 0.16, p = 0.003 / r = 0.15, p = 0.008). However, a CF ≥5 g and FTI ≥400 gs were associated with increased ΔLI compared to CF levels <5 g / FTI <400 gs (CF: p = 0.006, FTI: p = 0.008, Figure 1). Ablation sites in the right atrium displayed higher ΔLI when applying sufficient mean CF levels ≥5 g compared to the left atrium (22 (16-30) vs 16 (13-22) Ω, p = 0.008). Sufficient lesion formation was previously observed to be accomplished at a ΔLI ≥20 Ω, which was predicted best by baseline LI [odds ratio 1.07 (confidence interval 1.05-1.09), p < 0.001)] compared with CF [1.01 (0.97-1.05), p = 0.636], FTI [1.002 (1.00-1.003), p = 0.02] and local voltage [1.064 (0.76–1.4), p = 0.38].  Conclusion:  Simultaneous monitoring of LI and CF enables real-time analysis of (1) local catheter stability by pertaining CF levels beyond 5 g while concomitantly (2) characterising underlying substrate using the baseline LI and (3) estimating the effect of applied RF energy on lesion formation by assessing the ΔLI. This may enhance intra-procedural evaluation of effective RF delivery for tailored ablation procedures.